Brazil : Critical Issues in Social Security, Volume 2. Policy Report - World Bank (Washington, DC, 2013)
The study consists of two volumes, the first volume contains a detailed summary of the report findings, and policy implications, and, the second volume, the Policy Report, contains discussions on policy recommendations for each of the components of the Brazilian social security system. An overview on the dimensions of the social security challenge, reviews the system components, revealing unsustainable fiscal imbalances, and administrative weaknesses in both the unreformed General Regime for Social Security (RGPS), and the Pension Regime for Government Workers (RJU), with large tax-related distortions, and labor market inefficiency. Thus the goals of Brazil's reforms are to reduce fiscal deficits, lower actuarial imbalances, increase equity and redistribution, reduce collateral inefficiencies, and facilitate growth of funded pensions. The study implies there is no recourse for the country, but to lower the high, uniform replacement rates (experience suggests that rates higher than 40-70 percent, cannot be sustained) and, spells out that the key to effective reform of social security, is widening the debate to include potential winners from these changes, particularly the private sector, the young, and the poor. Policy recommendations suggest, that the adverse equity effects of RGPS reforms, should be widely publicized to generate political support for deeper RJU reform.